Study On Ramadan Fasting Towards Lipid Profiles And Total Antioxidant Status (Tas) Among Higher Ins Titution Learning Centre Staffs - Mohd Adzim Khalili, Rohin; Intan Suhana Munira, Mat Azmi; Dandinasivara Venkateshaiah, Muralidhara (2014)
The study was conducted to determine the changes of lipid profile and total antioxidant status (TAS) before, during and after Ramadan fasting among staffs in Institute of Higher Education, UniSZA. Methods:A total of 46 subjects were recruited (31% males and 69% females) ranging from the age of 25 to 40 years old. Information about socio-demographic data was obtained via questionnaire. Lipid profile and TAS were determined using Olympus AU-400 analyser machine and Cayman‟s Antioxidant Assay kit respectively. Results:The changes were detected in TC value, TG value, HDL- C value, and LDL- C value before, during and after Ramadan fasting. The TC value has shown significant changes at T2, T3 and T4 (p< 0.05). However, TG value was significantly changed only at T3 (p = 0.31). There was no significant difference in HDL-C value except the value was recorded to increase significantly at T3 (p=0.22). In contrast, significant changes in LDL- C was noted at T4 (p =0.01). TAS reading has shown no significant changes towards these three distinctive periods. However, there was significant difference of TAS value between male and female at T1 (p = 0.03). Conclusions:Ramadan fasting provides various information in evaluating lipid profile. This is hoped to help health professionals to construct strategic dietary intake during Ramadan.